Assessing the Gaps in Macro Skills: A Needs Analysis among Third-Year Psychology Students - Ngo, Cristy Grace A.; Reyes, Maria Shiela E.; Ganzon, Janica Rei T.; Felix, Daniella Joy G.; Bacaca, Julliana Amor P. (Journal Corner of Education, Linguistics, and Literature, 2024)
This quantitative study employed a needs analysis approach which aimed to identify, aid, and present the problem with the proficiency in reading, writing, speaking, and listening skills of third-year Psychology students. 50 respondents from the psychology department in a private non-sectarian academic institution were randomly surveyed to gather the requisite data. Results showed that the respondents need guidance across various language competencies. Their reading skills are at the frustration level, listening skills are at the proficient level, and writing and speaking skills are at the moderate level. This study suggests customized instructional approaches which can significantly improve the receptive and productive English language skills of third-year psychology students, thereby empowering them to achieve greater academic and professional success. These findings underscore the effectiveness of ESP programs in enhancing the language skills required for psychology students and of similar academic contexts.